Unregulated Foreign Investment Screening in Indonesia: State Sovereignty and Legal Certainty Implications - Rolis Barson Sembiring (Yayasan Cahaya Generasi Positif, 2026)
This article examines the regulatory vacuum in Indonesia regarding foreign direct investment screening mechanisms and its implications for state sovereignty and legal certainty. Despite the global paradigm shift towards national security screening, the current licensing system prioritizes economic facilitation, lacking an ex ante review procedure for strategic sectors. Utilizing doctrinal legal research with statute, conceptual, and comparative approaches, this study systematically analyzes the risks of this legislative void. The findings demonstrate that the absence of structured screening compromises national interests and degrades legal certainty. Arbitrary revocations of investments without established procedural frameworks expose Indonesia to international arbitration disputes under international investment agreements, risking fatal violations of the fair and equitable treatment standard. Consequently, this study concludes that Indonesia must urgently institutionalize a comprehensive investment screening system. This mechanism is absolutely imperative to proportionally balance open investment policies with essential security safeguards, thereby mitigating international litigation risks and protecting territorial sovereignty.